All-dielectric silicon metalens for two-dimensional particle manipulation in optical tweezers - Teanchai Chantakit; Christian Schlickriede; Basudeb Sain; Fabian Meyer; Thomas Weiss; Nattaporn Chattham; Thomas Zentgraf (My University, 2020)
Dynamic control of compact chip-scale contactless manipulation of particles for bioscience applications remains a challenging endeavor, which is restrained by the balance between trapping efficiency and scalable apparatus. Metasurfaces offer the implementation of feasible optical tweezers on a planar platform for shaping the exerted optical force by a microscale-integrated device. Here, we design and experimentally demonstrate a highly efficient silicon-based metalens for two-dimensional optical trapping in the near-infrared. Our metalens concept is based on the Pancharatnam-Berry phase, which enables the device for polarization-sensitive particle manipulation. Our optical trapping setup is capable of adjusting the position of both the metasurface lens and the particle chamber freely in three directions, which offers great freedom for optical trap adjustment and alignment. Two-dimensional (2D) particle manipulation is done with a relatively low numerical aperture metalens ($NA_{ML}=0.6$). We experimentally demonstrate both 2D polarization sensitive drag and drop manipulation of polystyrene particles suspended in water and transfer of angular orbital momentum to these particles with a single tailored beam. Our work may open new possibilities for lab-on-a-chip optical trapping for bioscience applications and micro to nanoscale optical tweezers.
Keywords: Optical force; Tweezers; Particle (ecology); Orbital Angular Momentum in Optics